Експериментальний зразок обладнання для потокового внесення компонентів у кормосуміші - Парієв, А. О.; Дробишев, О. О.; Коротченко, Т. М.; Сиротюк, С. В.; Болтянський, Борис Володимирович; Болтянский, Борис Владимирович; Boltianskyi, Borys (My University, 2021)
UK: Розроблено експериментальний зразок обладнання для потокового внесення компонентів кормів в процесі їх роздавання та проведено експериментальні дослідження. Перевагою розроблюваного обладнання є те, що його можна встановити на серійний кормороздавач типу КТУ-10, що забезпечить технологічний процесс потокового внесення компонентів з можливістю рівномірно вносити компоненти у кормосуміш, а також мобільність, простота конструкції і невелика вартість. Обладнання для потокового внесення компонентів кормів в процесі їх роздавання забезпечить зниження питомих витрат на приготування і роздачу кормів на 45 %, час приготування кормосуміші на 30 %, собівартість виробництва молока на 2,8 %, питомої матеріаломісткості обладнання з 430 кг/м3 до 260 кг/м3.. Орієнтований річний економічний ефект від використання одного кормороздавача КТУ-10 з технічним засобом для потокового внесення компонентів у порівнянні з кормороздавачем СРК-10 складає 13,3 тис. грн. Строк окупності до 1,5 року. EN: An experimental sample of equipment for streaming of feed components in the process of their distribution was created. The constructive feature of the experimental sample equipment for streaming - an active working body consists of two parts - a spiral screw and a drum with blades. The drum with blades is executed with a screw skill, which coincides with the direction of a spiral screw. The technological feature - the concovines bunker is provided with a septum, which shares it into two parts, and two unloading windows with dosage. This provides the technological process of streaming simultaneously 2 components of concentrated feeds with the ability to accommodate components in feed mix. Experimental studies of bunker equipment for streaming of feed components with two dosing operations are carried out: slide shivers with a spiral screw and drum dispenser with screw blades and a rotary valve, and a bunker, which is equipped with a septum and two dosing windows. According to experimental studies, the equipment for streaming of feed components is determined that the productivity and uniformity of the production of components of bulk feed in the stream are from 0,3 to 3,5 kg / m in a variation of 4-11%. The optimal structural and technological parameters of equipment for streaming are determined. The oriented annual economic effect of using one feeder CTU-10 with a technical means for streaming components in comparison with the feeder SRK-10 is 13,3 thousand UAH. Payback period up to 1,5 years. Equipment for streaming of feed components in the process of their distribution will provide a decrease in specific costs for preparation and distribution of feed by 45%, the preparation of feed mixing by 30%, the cost of milk production by 2,8%, specific material content of equipment with 430 kg / m3 260 kg / m3. RU: Разработан экспериментальный образец оборудования для потокового внесения компонентов кормов в процессе их раздачи и проведены экспериментальные исследования. Преимуществом разрабатываемого оборудования является то, что его можно установить на серийный кормораздатчик типа КТУ-10, что обеспечит технологический процесс потокового внесения компонентов с возможностью равномерно вносить компоненты в кормосмеси, а также мобильность, простота конструкции и небольшая стоимость. Оборудование для потокового внесения компонентов кормов в процессе их раздачи обеспечит снижение удельных затрат на приготовление и раздачу кормов на 45%, время приготовления кормосмеси на 30%, себестоимость производства молока на 2,8%, удельной материалоемкости оборудования с 430 кг/м3 до 260 кг/м3. Ориентированный годовой экономический эффект от использования одного кормораздатчика КТУ-10 с техническим средством для потокового внесения компонентов по сравнению с кормо-раздатчиком СРК-10 составляет 13,3 тыс. грн. Срок окупаемости до 1,5 года.
Experimental sample of equipment for flow introduction of components in the feed
Экспериментальный обрацец оборудования для потокового внесения компонентов в кормосмеси
Keywords: обладнання; потокове внесення; кормосуміш; експериментальні дослідження; конструкційно-технологічні параметри; equipment; flow application; feed mixture; experimental research; construction and technological parameters; оборудование; потоковое внесения; кормосмеси; экспериментальные исследования; конструкционно-технологические параметры